Handling with online comments: a longitudinal approach in most accessed news sites in Portugal, Spain and Brazil - Ribeiro, Fábio (2020)
Online comments have been a widespread feature in news media. Although audiences recognize it widely, doubts remain about the purpose of these interactive spaces. Arguably, understanding how media value online comments defines a way which public debates are socially perceived. Based on The Reuters Institute Digital News Report 2019, this article analysed current media policies towards online commenting in most accessed news websites in Portugal, Spain and Brazil. Following both a quantitative-qualitative methodology, a direct observation and a textual/visual analysis, this article highlights levels of similarity in these policies: comment sections are still predominantly available (31 from 45); comments are typically placed at the bottom of the page; the interactive options identical (share, like, dislike, report). As the overall cases exclude comment moderation, few media (in Portugal, but mostly in Spain) propose alternative models based on the community: voting, comment ranking and autonomous discussion forums.